Chemistry contribution to stratospheric ozone depletion after the unprecedented water‐rich Hunga Tonga eruption - Zhang, Jun (author); Kinnison, Douglas (author); Zhu, Yunqian (author); Wang, Xinyue (author); Tilmes, Simone (author); Dube, Kimberlee (author); Randel, William (author) (Geophysical Research Letters, 2024)
Following the Hunga Tonga-Hunga Ha'apai (HTHH) eruption in January 2022, stratospheric ozone depletion was observed at Southern Hemisphere mid-latitudes and over Antarctica during the 2022 austral wintertime and springtime, respectively. The eruption injected sulfur dioxide and unprecedented amounts of water vapor into the stratosphere. This work examines the chemistry contribution of the volcanic materials to ozone depletion using chemistry-climate model simulations with nudged meteorology. Simulated 2022 ozone and nitrogen oxide (NOx = NO + NO2) anomalies show good agreement with satellite observations. We find that chemistry yields up to 4% ozone destruction at mid-latitudes near similar to 70 hPa in August and up to 20% ozone destruction over Antarctica near similar to 80 hPa in October. Most of the ozone depletion is attributed to internal variability and dynamical changes forced by the eruption. Both the modeling and observations show a significant NOx reduction associated with the HTHH aerosol plume, indicating enhanced dinitrogen pentoxide hydrolysis on sulfate aerosol. 1852977 80NSSC19K0952